A Narrative Inquiry into an EFL Teacher: How is the ICT Used to Optimize Project-based Learning? - Hana Azmi Zakiyyah Mustaqimah; Puji Astuti; Sri Wahyuni (English Education Journal, 2023)
Internet and technology innovation has traditionally been employed in education as a learning and teaching tool. Research and publications also have been examined and found to be associated with significant outcomes. In today’s age, technology and the internet have its own place in education, forcing students to employ 21st-century technology skills. Meanwhile, the other research reports that project-based learning (PjBL) is open-ended, allowing students to incorporate even more technology. This narrative inquiry research reports the stories based on the teacher’s experience in integrating technology and the internet in PjBL. The stories were collected through written (i.e., narrative frame) and oral narratives (i.e., face-to-face semi-structured interviews) and conducted using Bahasa Indonesia to explore the stories in detail. The open-ended questions adequately facilitated our exploration of the teacher’s stories. We found that learning activities in “Local Wisdom” PjBL incorporate technology and the internet under two themes: technology and the internet are used to access knowledge and information and to create media products. The stories told could remind teachers that the use of technology and the internet in PjBL is not only limited to a mediator for delivering the material; this could galvanize the teachers into involving students to be more active in using technology and the internet.